Family Factors Related to Stunting: Number of Family Members, Mother's Education Level, and Working Mother in Children aged 24-59 Months in Sungai Penuh City, Jambi Province, Indonesia - Nashira, Illiyin Tri; Kusnandar; Sukamto, Ika Sumiyarsi (Future Science, 2024)
Stunting in toddlers can cause lost generations. One of the factors that influence the occurrence of stunting is family factors. Stunting can be influenced by the number of family members in a household, which affects the amount of income and the amount of nutritional intake that must meet individual needs. In addition, mothers have had a crucial part in raising children mothers have an important role in caring for children, providing nutritious food, and nurturing children, so maternal knowledge and the time mothers spend caring for children can affect the nutritional status of toddlers. To identify the determinants of stunting, a cross-sectional design method was used with a sample size of 230 children aged 24-59 months in Sungai Penuh City, Jambi Province. Stunting was the dependent variable, whereas family size, the mother's occupation, and level of schooling were the independent variables. The main data source was the results of SSGI 2022. It is anticipated that the use of national survey data, the chi-square test, and logistic regression analysis with a 95% confidence level will help discover familial characteristics linked to stunting. The study's findings demonstrated that mother education was a contributing and predictive factor of stunting to the incidence of stunting in toddlers aged 24-59 months (p-value <0.05). However, the number of family members and working mother status showed negative predictor values. It is anticipated that this research will contribute and offer answers to resolving the gaps that occur in society in reducing stunting rates in Indonesia, especially in policy making.